Hadith #2279 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق (Sunan Abi Dawud)
This tradition has been narrated by ‘Abd Al Rahman bin Abi Laila through a different chain of narrators. This version has “He decided that she would be given to Ja’far and said “Her maternal aunt is with him(i.e., his wife).
Grade: Sahih

Hadith #3204 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Musa al-Asha'ari; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave the people news of death of Negus on the day on which he died, took them out to the place of prayer, drew them up in rows and said: “Allah is Most Great” four times.
Grade: Sahih

Hadith #3669 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Umar ibn al-Khattab (Sunan Abi Dawud)
The prohibition of wine came down when (the Quranic verse ) came down. It was made from five thing namely, grapes, dates, honey, wheat ,barley. Wine is what infects (khamara) the mind. There are three things I wished that the prophet (ﷺ) would not leave us until he explained them fully to our satisfaction: (share of) grandfather, one who leaves no descendants or ascendants as hairs, and the details of usury.
Grade: Sahih

Hadith #4359 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; ibn Abbas; Ikrama عكرمة; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Uthman al-Shham al-Dwy Abu عثمان الشحام العدوي أبو سلمة البصري يقال (Sunan Abi Dawud)
On the day of the conquest of Mecca, Abdullah ibn Sa’d ibn AbuSarh hid himself with Uthman ibn Affan. He brought him and made him stand before the Prophet (ﷺ), and said: Accept the allegiance of Abdullah, Messenger of Allah! He raised his head and looked at him three times, refusing him each time, but accepted his allegiance after the third time. Then turning to his companions, he said: Was not there a wise man among you who would stand up to him when he saw that I had withheld my hand from
Grade: Sahih

Hadith #5139 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abdullah bin 'Amr bin al-'Aas; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن (Sunan Abi Dawud)
I said: Messenger of Allah! to whom should I show kindness? He replied: Your mother, next your mother, next your mother, and then comes your father, and then your relatives in order of relationship. The Messenger of Allah (ﷺ) said: If a man asks his slave whom he freed for giving him property which is surplus with him and he refuses to give it to him, the surplus property which he refused to give will be called on the Day of resurrection as a large bald snake. Abu Dawud said: Aqra’ means a s
Grade: Hasan Sahih